2016
DOI: 10.1007/s00167-016-4036-y
|View full text |Cite
|
Sign up to set email alerts
|

Ischiofemoral impingement: defining the lesser trochanter–ischial space

Abstract: The lesser trochanter is closest to the ischium in lateral rotation and is furthest away in medial rotation when the hip is in neutral flexion-extension/abduction-adduction. The lesser trochanter approximates the ischium when the hip is laterally rotated in 10° extension and adduction. The information gained through this investigation helps to define the pathomechanics associated with ischiofemoral impingement and validate clinical tests to diagnose ischiofemoral impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
5
41
0
Order By: Relevance
“…2 It seems that the pain occurs when the quadratus femoris muscle is entrapped in narrow space between the ischial tuberosity and the lesser trochanter. 3 In this situation, the sciatic nerve can be also entrapped or compressed by quadratus femoris, which results in shortened stride and pain while sitting on a hard surface.…”
Section: See Commentary On Page 156mentioning
confidence: 99%
See 1 more Smart Citation
“…2 It seems that the pain occurs when the quadratus femoris muscle is entrapped in narrow space between the ischial tuberosity and the lesser trochanter. 3 In this situation, the sciatic nerve can be also entrapped or compressed by quadratus femoris, which results in shortened stride and pain while sitting on a hard surface.…”
Section: See Commentary On Page 156mentioning
confidence: 99%
“…The scan time ranged from 9 to 11 minutes. Because IFD is significantly influenced by hip position, 3 hips were kept in extension, and knees were kept in extension and neutral rotation with patella facing anteriorly. Positioning band was applied to maintain the position during CT scanning.…”
Section: Ct Measurement Protocolmentioning
confidence: 99%
“…A combined position of hip extension, adduction, and lateral rotation has been shown to decrease the ischiofemoral distance. 14,15 Kivlan et al 15 showed a decrease in the ischiofemoral distance by over 50% when the hip was taken toward the end range of lateral rotation with the hip in neutral flexion-extension and abduction-adduction. Singer et al 16 used dynamic magnetic resonance imaging to show how the ischiofemoral distance decreases through an arc of lateral rotation.…”
Section: See Commentary On Page 150mentioning
confidence: 99%
“…5 The sciatic nerve can be entrapped in ischiofemoral impingement between the ischium and lesser trochanter. 6,7 Also at the level of the ischium, the proximal hamstring can be involved in sciatic nerve entrapment and is known as ischial tunnel syndrome. 6,8 ( Figure 1) The pudendal nerve can be entrapped in several locations as it exits the greater sciatic foramen, travels over the sacrospinous ligament, traverses through the pudendal canal (also known as Alcock's canal) formed by the obturator fascia and sacrotuberous ligament, and emerges inferior to the pubic bone to innervate the perineum and genetalia.…”
Section: Posterior Nerve Entrapmentsmentioning
confidence: 99%
“…7 The active knee flexion tests at 30° and 90° have been described for assessment of proximal hamstring tendon pathology and ischial tunnel syndrome. 6 These tests are performed while the patient is seated and their knee positioned in 30° flexion (Figure 6-A) and then in 90° flexion (Figure 6-B) with the examiner palpating the ischial tunnel.…”
Section: Figure 2 Pathway Of the Pudendal Nerve (Highlighted In Yellmentioning
confidence: 99%